Stroke in geriatric patients admitted to the intermediate care of internal medicine - Rafael Venegas Rodríguez; Wilfredo Hernández Pedroso; Daily Chacón Montano; Ricardo González Mesana; Raúl Santana Sánchez; Efraín Chibás Ponce (Revista Cubana de Medicina Militar)
Introduction: The knowledge and control of the stroke patient can contribute to improve the prognosis. Objective: To characterize geriatric patients with stroke, who enter the intermediate care unit of medicine. Methods: an observational and cross-sectional study was carried out, in geriatric patients admitted with stroke, in the medicine intermediate care room of the Hospital Militar Central Dr. Luis Díaz Soto. The universe was 680 patients with the clinical and imaging diagnosis of stroke. Variables studied were: age, sex, clinical forms, NIHSS indexes, personal pathological history, morbidity, lethality, and dependency status. Results: The ischemic form predominated (94%), the age from 65 to 74 years (40%), the male sex (61.5%) and the NIHSS index less than 20 points (82.7%). High blood pressure, previous cerebrovascular disease and diabetes mellitus were the most frequent antecedents. The lethality was 10.0% and the most frequent complication was bronchopneumonia (16.9%). 40% presented a state of total dependency. Conclusions: Patients were characterized by the predominance of the ischemic form, of the male sex, age between 70 and 79 years, and bronchopneumonia as a complication. The high NIHSS index was associated with an unsatisfactory evolution and although the overall case fatality was not high, the presence of the state of total dependence was important. This requires significant rehabilitation work to achieve an acceptable quality of life.